Psychotic syndrome associated with anti-Ca/ARHGAP26 and voltage-gated potassium channel antibodies - Jarius, Sven; Wildemann, Brigitte (Journal of neuroimmunology, 2015)
Background - Antibodies to the Rho GTPase-activating protein 26 (ARHGAP26, GRAF1) (also termed anti-Ca) were first described in patients with cerebellar ataxia. However, ARHGAP26 is also expressed in some hippocampal neurons. Moreover, some of the previously reported patients showed cognitive and affective symptoms. It is unknown whether those symptoms reflected involvement of the limbic system or were part of the so-called cerebellar cognitive/affective syndrome. - Case report - Here, we report a newly diagnosed anti-Ca/ARHGAP26-IgG-positive patient who presented with recurrent psychotic symptoms but no cerebellar ataxia. In addition, low-titer acetylcholine receptor antibodies, voltage-gated potassium channel complex antibodies (but no LGI1 or CASPR2 antibodies) and anti-nuclear antibodies of unknown specificity were detected, suggesting a general autoimmune predisposition. Thymectomy revealed mild thymic nodular hyperplasia. - Conclusion - This case indicates that the clinical spectrum of ARHGAP26-related autoimmunity might be broader than expected. Studies on the prevalence of anti-Ca/ARHGAP26 in patients with suspected limbic encephalitis seem warranted.